Neuroeducation in Early Childhood Education: A Neuroscience Approach to Optimizing Cognitive Development in Young Children - Fikri, Mu'tasim; Indriawati, Ratna (Journal of Gemilang, 2026)
Early childhood represents a critical period of brain development characterized by high neuroplasticity, during which neural connections rapidly form and are highly responsive to environmental stimulation. Neuroscience research emphasizes that appropriate learning experiences during this “golden period” can significantly influence children’s cognitive, emotional, and social development. However, many early childhood education practices still lag behind advances in neuroscience, creating a gap between scientific knowledge about how the brain learns and classroom practices. This study aims to analyze how neuroeducation, as an interdisciplinary approach integrating neuroscience and education, can optimize cognitive development in early childhood education. The research employs a qualitative approach using a systematic literature review of accredited scientific journal articles related to neuroscience, neuroeducation, and early childhood learning. Data were collected from relevant academic publications and analyzed using qualitative content analysis and conceptual synthesis techniques. The findings indicate that neuroeducation-based learning strategies such as play-based learning, music activities, socio-emotional learning, and early numeracy stimulation contribute significantly to strengthening neural connectivity and improving children’s executive functions and cognitive abilities. However, the implementation of neuroscience-informed practices remains limited due to insufficient teacher training and the persistence of traditional pedagogical approaches. The study concludes that integrating neuroeducation principles into teacher preparation and curriculum design is essential to effectively utilize the sensitive period of early brain development and support optimal cognitive development in young children.